The Effect of Hedonic Shopping Value and Impulsive Buying on Flash Sale - Abror, Mohammad (Master of Management Diponegoro University, 2023)
The research purpose is to assess effects of hedonic shopping value and impulsive buying on flash sale. Online questionnaires were used to collect the data for this research, which resulted in 286 valid questionnaires. Analysis shows novelty, escapism, and impulsive buying dimensions of hedonic shopping value positively affect discounted product purchasing intention on flash sale. During flash sale, high intensity shopping activities while consumers focus more on the low prices or entertainment value. Meanwhile there are no studies In Indonesia that assess consumers shopping behavior towards flash sale. For this reason, the research is originally to contribute to the literature.